PERTUMBUHAN SENGON SOLOMON DAN RESPONNYA TERHADAP PENYAKIT KARAT TUMOR DI BONDOWOSO, JAWA TIMUR - Dedi Setiadi; Liliana Baskorowati; Mudji Susanto (Jurnal Pemuliaan Tanaman Hutan, 2014)
A provenance stands of sengon Solomon (Falcataria moluccana (Miq.) Barneby & JW Grimes was establishhed in Bondowoso, East Java in 2011. One provenance seed consisting of 25 families originated from Solomon Island were used in this trial. Provenance stands was designed by rows column design (incomplete block) involving 8 blocks, 4 trees per plot (plot tree) with a spacing of 3 m x 2 m. Several characters were observed i.e: survival rate, height, diameter and the presence of gall rust diseases; the observations were undertaken every 6 months from 6 months old up to the age of 18 months. The results showed that the mean of survival rates ranging from 75% to 90%; with the average survival rate of 84.83% (6 months), 83.26% (12 months) and 81.05% (18 months). The mean height and diameter of 6 months old (2.42 m, 2.97 cm), 12 months old (4.74 m, 5.56 cm), and 18 months old (7.35 m, 7.39 cm). Varian analysis of height, diameter, disease severity and intensity showed that there were no significant differences between families. All of families attacked by gall rust disease, however family number 2, 8 and 23 showed the lowest respond of attack compared to other families. Therefore, those families can be recommended for future development in terms of toleration to the gall rust disease.